2020
DOI: 10.1186/s12891-020-03214-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic treatment regimens for bone infection after debridement: a study of 902 cases

Abstract: Background: Our aim was to investigate the clinical efficacy and complications of antibiotic treatment regimens for patients with bone infection. Methods: We retrospectively analysed patients with bone infection admitted to our hospital between March 2013 and October 2018. After surgical debridement was performed, the patients were divided into three groups: IV group (intravenous antibiotics for 2 weeks); oral group (intravenous antibiotics for 2 weeks followed by oral antibiotics for 4 weeks); and rifampicin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Therefore, the findings from implant-associated infection studies may not be directly applicable to native bacterial osteomyelitis, and more research is needed. In our research, some RCTs showed improved treatment outcomes with the addition of rifampicin [12,38,43,44] with non-statistically significant results, while others observed no significant difference [35,40,41,45]. Common limitations of studies included: investigation of S. aureus bacteremia without separate analysis of patients with osteomyelitis [36,37], small size, exclusion of patients with comorbidities [40,41], unbalanced arms in terms of size [43,44] or different patient comorbidities in study arms [38,43,44].…”
Section: Combination Antibiotic Therapy With Rifampicin Vs Antibiotic...mentioning
confidence: 66%
“…Therefore, the findings from implant-associated infection studies may not be directly applicable to native bacterial osteomyelitis, and more research is needed. In our research, some RCTs showed improved treatment outcomes with the addition of rifampicin [12,38,43,44] with non-statistically significant results, while others observed no significant difference [35,40,41,45]. Common limitations of studies included: investigation of S. aureus bacteremia without separate analysis of patients with osteomyelitis [36,37], small size, exclusion of patients with comorbidities [40,41], unbalanced arms in terms of size [43,44] or different patient comorbidities in study arms [38,43,44].…”
Section: Combination Antibiotic Therapy With Rifampicin Vs Antibiotic...mentioning
confidence: 66%
“…[105] Antibiotic therapy is the most primary and traditional method for combating bacteria. [105,106] However, the presence of biofilm impedes the permeation of antibiotics, and the administration of antibiotics tends to readily elicit bacterial resistance due to their specific and limited target sites. [107,108] In contrast, biomaterials are difficult to trigger bacterial tolerance because biomaterials have many passive antibacterial mechanisms, which contain direct cell wall or membrane destruction, ROS production, and intracellular components damage.…”
Section: Therapeutic Strategies Based On Pathogens Eliminationmentioning
confidence: 99%
“…Until now, repairing infected jaw defects has remained a challenge due to its high recurrence rate for oral and maxillofacial surgeons ( Zhang et al, 2019 ). To our knowledge, infection is due to the local presence of pathogenic bacteria in the lesion, and once an infected jaw defect occurs, it may require multiple surgical debridements and long-term systemic antibiotic therapy, which may lead to the development of secondary injury, adverse antibiotic reactions, or lifelong functional impairment, and increase the financial burden on the health-care system ( Vestby et al, 2020 ; Wang et al, 2020 ). Therefore, antimicrobial drug carriers, a topical strategy, have become an adjunct to the prevention and treatment of infections in jaw defects ( Alazzawi et al, 2021 ; Han et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%